From supply chains towards manufacturing ecosystems: A system dynamics model - Kazantsev, Nikolai; Petrovskyi, Oleksii; Müller, Julian (Technological Forecasting and Social Change, 2023)
Rapid market changes call for demand-driven collaborations in manufacturing, which trigger supply chain evolution to more distributed supply structures. This paper explores the system dynamics of the largest European aerospace manufacturer's supply chain. We conceptualise a manufacturing ecosystem by observing the impacts of supplier development, digital platforms, smart contracting, and Industry 4.0 on demand-driven collaborations in time. We contribute to the literature on ecosystem strategy, particularly for regulated industries, by disclosing the role of demand-driven collaborations in supporting the ecosystems' growth. We provide manufacturing firms with an open-access tool to exemplify their ecosystem development and produce initial training datasets for AI/ML algorithms, supporting further analytics.
Created from Fastlane, Scopus look-up
Keywords: Aerospace; Demand-driven collaboration; Industry 4.0; Manufacturing ecosystem; SME; System dynamics